On effecting averages nad changes of scale via weighting functions - Murdoch, A.I. (Archives of Mechanics, 1998)
Weighting functions can be used to derive continuum equations of balance from molecular considerations, and to obtain equations governing fluid flow through porous media. The methodology of such (scale-dependent) averaging is outlined, and physical implications of specific choices of weighting function are discussed.